Crosstalk between cytotoxic CD8+ T cells and stressed cardiomyocytes triggers development of interstitial cardiac fibrosis in hypertensive mouse hearts - Brassington, Kurt; Kanellakis, Peter; Cao, Anh; Toh, Ban-Hock; Peter, Karlheinz; Bobik, Alex; Kyaw, Tin (Frontiers in Immunology, 2022)
Aims: Cardiac fibrosis is central to heart failure (HF), especially HF with preserved ejection fraction (HFpEF), often caused by hypertension. Despite fibrosis causing diastolic dysfunction and impaired electrical conduction, responsible for arrhythmia-induced sudden cardiac death, the mechanisms are poorly defined and effective therapies are lacking. Here we show that crosstalk between cardiac cytotoxic memory CD8+ T cells and overly stressed cardiomyocytes is essential for development of non-ischemic hypertensive cardiac fibrosis. Methods and Results: CD8 T cell depletion in hypertensive mice, strongly attenuated CF, reduced cardiac apoptosis and improved ventricular relaxation. Interaction between cytotoxic memory CD8+ T cells and overly stressed cardiomyocytes is highly dependent on the CD8+ T cells expressing the innate stress-sensing receptor NKG2D and stressed cardiomyocytes expressing the NKG2D activating ligand RAE-1. The interaction between NKG2D and RAE-1 results in CD8+ T cell activation, release of perforin, cardiomyocyte apoptosis, increased numbers of TGF-β1 expressing macrophages and fibrosis. Deleting NKG2D or perforin from CD8+ T cells greatly attenuates these effects. Activation of the cytoplasmic DNA-STING-TBK1-IRF3 signaling pathway in overly stressed cardiomyocytes is responsible to elevating RAE-1 and MCP-1, a macrophage attracting chemokine. Inhibiting STING activation greatly attenuates cardiomyocyte RAE-1 expression, the cardiomyocyte apoptosis, TGF-β1 and fibrosis. Conclusion: Our data indicate that cytotoxic cardiac CD8+ T cell innate signaling together with cardiomyocyte STING signaling are critical for hypertensive fibrosis; preventing CD8+ T cell activation by inhibiting the cardiomyocyte RAE-1-CD8+ T cell-NKG2D axis holds promise for novel therapeutic strategies to limit hypertensive cardiac fibrosis.